Anantrum gallopintoi sp. nov. (Bothriocephalidae Blanchard, 1849), a cestode parasite of the shorthead lizardfish Synodus scituliceps (Synodontidae) from the Pacific coast of Costa Rica - Santoro, Mario (2024)
A new species of bothriocephalid cestode in the genus Anantrum is described from the intestine of the shorthead lizardfish Synodus scituliceps from the north Pacific coast of Costa Rica. The new species is described based on an integrative taxonomic approach that includes the use of light and scanning electron microscopy, 28S rDNA sequencing, and phylogenetic analysis. Anantrum gallopintoi sp. nov. is the third known member of this genus and can be distinguished from A. tortum (Linton, 1905) and A. histocephalum Jensen & Heckmann, 1977 by a combination of morphological and ecological traits and, in particular, by having a vaginal sphincter, different number of testes, and different type host and type locality. The molecular analysis and the phylogenetic reconstructions supported its status as a new taxon placing it within a well-supported separate branch of Anantrum spp. subclade. According to the present finding, S. scituliceps represents a new host record and Costa Rica a new geographical record for Anantrum species, and, in general, for a bothriocephalid cestode.